NATURAL AND ANTROPIC TOURIST POTENTIAL IN TRANSILVANIA - Daniela PLEȘOIANU; Edith GRECU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This paper is an analysis of Transylvania regarding the natural and anthropic potential of the Transylvania region. In this paper we used methods such as cartographic description, analytical method and graphics. These methods helped to translate data into charts, tables and charts using the EXCEL program. The paper is based on documentation, analysis of statistical and territorial data research, integration and complex interpretation of information. The integration of all geographic information allowed, through complex interpretation and their transposition into representative maps, the knowledge and understanding of the natural and anthropic tourism potential in Transylvania. The data used were provided by the following institutions: Counties Councils, County Development Strategy 2007 - 2013, National Institute of Statistics, ADR Central analysis "Balnear tourism-economic domain with potential development in the Center Region". Regarding the natural tourist potential of the area within the region, there are natural and national parks (eg Cheile Bicazului-Hăşmaş National Park), nature reserves (eg Aiud Cheile, Cheile Râmeţului, Cheile Întregalde), winter resorts (eg: Predeal, Păltiniş) and spa resorts. The cultural and historical heritage is also complex and includes ancient vestiges (eg: The remains of the Roman castles Apulum), cities with a complex cultural heritage (eg Brasov, Sibiu), fortified churches and fortresses (eg Prejmer Church, Viscri, Saschiz, Rupea Fortress, Râşnov Fortress), castles and palaces (eg Bran Castle, Brukenthal Palace), monasteries (eg Sâmbăta de Sus).